The Sub Acute Toxicity Study of Purified Gambir (Uncaria gambir Roxb.) to Liver Histology and its Reversibility on Rats - Dita Permatasari; Indri Oktavia; Armenia Nazar; Almahdy Ahmadin (Bioscience, 2021)
Purified gambir proved to have many pharmacological activities and has the potential to be developed into standardized herbal medicines. This study was conducted to determine the safety of purified gambir to the liver histology. A total of 30 female white rats were used which divided into 4 groups: one control group and 3 test groups treated with purified gambir at doses of 5, 10 and 20 mg/kgbw orally for 14 days respectively. On the scheduled days, three animals from each group were killed for liver histological examination. The degree of liver damage and liver organ ratio in this study where were measured. The reversibility of liver damage was observed from the change in the value of the damage degree and liver organ ratio after the administration of gambir was stopped. Data were analyzed using two-way ANOVA followed by Duncan (significance were taken at p<0.05). The administration of purified gambir in rats for 14 days at tested groups caused significant damage to liver tissue (p<0.05). In this situation, the degree of tissue damage increased and the liver organ ratio decreased in all tested groups. After the administration was stopped, the degree of liver damage is decreased insignificantly, meanwhile the liver organ ratio is significantly increased.